Acute Kidney Injury Incidence in COVID-19 Patients Receiving Remdesivir Therapy at Awal Bros Panam Hospital - Reslina, Ade Novita; Monita, Faradilla; Sembiring, Ligat Pribadi (Indonesian Journal of Kidney and Hypertension, 2024)
Background: Remdesivir is one of the pharmacological therapies for moderate COVID-19 patients. Remdesivir is an antiviral that can increase the risk of nephrotoxicity. Objective: The study aims to evaluate the incidence of acute kidney injury (AKI) in COVID-19 patients receiving remdesivir. Methods: This is a cross-sectional analytic study of 238 COVID-19 patients receiving remdesivir therapy at Awal Bros Panam Hospital for the period 2020–2022. AKI was diagnosed using the KDIGO criteria. The chi-square test was used to determine the correlation of AKI incidence with age, gender, and comorbidities, with a significance level of p < 0.05. Results: AKI was found in 32 patients (13.4%). The majority of AKI patients (75%) were aged 60 years or older, with 65.6% being male. Additionally, 84.4% of these patients had comorbidities, and 53.1% of them died. Around half of the patients were diagnosed with stage 1 AKI, and the majority, specifically 84.4%, did not undergo renal replacement therapy (RRT). The association between the incidence of AKI and age and comorbidities was shown to be statistically significant (p=0.000; RR 5.11; 95% CI 2.44-10.8 and p=0.009; RR 3.05; 95% CI 1.22-7.64, respectively). Conclusion: The main risk factors for AKI are primarily observed in the older population and individuals with several medical conditions. Greater emphasis should be placed on administering remdesivir to COVID-19 patients who are elderly and have comorbidities, as they are at a higher risk of developing AKI.